2021
DOI: 10.1111/rec.13486
|View full text |Cite
|
Sign up to set email alerts
|

Participatory active restoration of communal forests in temperate Himalaya, India

Abstract: Potential of community participation and non-timber forest species in forest restoration has been widely discussed but rarely demonstrated through long-term empirical studies. An attempt was made to restore the communal forest in temperate Indian Himalaya by mixed planting of multipurpose broad-leaved trees, bamboo, and medicinal herbs chosen by local people based on pooled indigenous and scientific knowledge. Funding was terminated after 7 years, while people-researcher interactions and monitoring of the rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…This Section summarizes details in previous studies in the same sites (Rao et al, 1999(Rao et al, , 2022 2.1 Study village Khaljhuni (30 0 13'5'' N latitude, 80 0 6' 35'' E longitude) is a typical of remote village around UNESCO World Heritage Nanda Devi Biosphere Reserve in the State of Uttarakhand, India (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This Section summarizes details in previous studies in the same sites (Rao et al, 1999(Rao et al, , 2022 2.1 Study village Khaljhuni (30 0 13'5'' N latitude, 80 0 6' 35'' E longitude) is a typical of remote village around UNESCO World Heritage Nanda Devi Biosphere Reserve in the State of Uttarakhand, India (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…A generic anticipation was that successful trials would entail voluntary maintenance/upscaling/outscaling and policies favouring them. Extending our previous work in temperate Himalaya (Rao et al, 1999(Rao et al, , 2003(Rao et al, , 2022, the present study provides an account of on-site, off-site and village landscape scale ecological (viz., vegetation structure, owering plant diversity and carbon stocks), economic (viz., yields and income) and social (viz., equity and solidarity) outcomes over a period of 13 years after 7-year-long funding phase in a remote temperate village landscape.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Thereby, all steps across the entire initiative must be discussed, agreed, planned, and executed with locals and their representative associations. Such a protagonism/empowering based on reciprocal relationships among stakeholders or participatory active restoration (Rao et al 2022) is critical to guarantee restoration engagement, equity, and effectiveness (Löfqvist et al 2023). It is also in accordance with the required connections between global changes, vulnerable populations and human rights since a safe, clean, healthy, and sustainable environment is a fundamental human right, but gains and losses from global changes are unequally distributed as postulated by the Climate Justice approach (Sultana 2022).…”
Section: Addressing Forest Fires Via An Integrated Research Agendamentioning
confidence: 99%
“…Gopalakrishna et al (2022) reported that 1.58 million ha of land in India is suitable for restoration, for a potential of 61.3 Tg of carbon sequestration. Forest restoration may also improve the lives of forest‐dependent people (Rao et al, 2021), but recent studies have reported widespread restoration failures (Coleman et al, 2021; Asher & Bhandari, 2021). This review article seeks to understand the historical development of restoration practices in India to better understand why contemporary practices are failing, and what can be done about it.…”
Section: Introductionmentioning
confidence: 99%